Cultures of voting in pre-modern Europe
1 online resource (xi, 176 pages)
Keywords: "Cultures of Voting in Pre-modern Europe examines the norms and practices of collective decision-making across pre-modern European history, east and west, and their influence in shaping both intra- and inter-communal relationships. Bringing together the work of twenty specialist contributors, this volume offers a unique range of case studies from Ancient Greece to the eighteenth century, and explores voting in a range of different contexts with analysis that encompasses constitutional and ecclesiastical history, social and cultural history, the history of material culture and of political thought. Together the case-studies illustrate the influence of ancient models and ideas of voting on medieval and early modern collectivities and document the cultural and conceptual exchange between different spheres in which voting took place. Above all, they foreground voting as a crucial element of Europe's common political heritage and raise questions about the contribution of pre-modern cultures of voting to modern political and institutional developments. Offering a wide chronological and geographical scope, Cultures of Voting in Pre-modern Europe is aimed at scholars and students of the history of voting and is a fascinating contribution to the key debates that surround voting today. "--Provided by publisher.